Performance Appraisal By Balanced Scorecard: A Case Study Of Iran Khodro Diesel - Tahbaz, Ardeshir Valadan (2008)
In this paper, first we look at the balanced scorecard as a measurement tool of the company's industrial position with regards to its competitors. Then some metrics are suggested for measuremnt and based on them the company's system is analyzed.